Pengaruh Kompensasi, Kepuasan Kerja dan Fleksibilitas Terhadap Kinerja Driver Go-Ride Wilayah Sedati Sidoarjo - Intan Puspita Dewi; Rusdi Hidayat Nugroho (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This study aims to determine how much influence Compensation, Job Satisfaction and Flexibility have on the Performance of Go-Ride Drivers in the Sedati Sidoarjo Region. This study uses descriptive quantitative methods using the Accidental Sampling approach and the data involved is primary data with a total number of respondents of 100 respondents Go-Ride Driver Sedati Sidoarjo Region. The independent variables in this study include compensation, job satisfaction and flexibility, while the dependent variable is performance. The test instruments used are Validity Test and Reliability Test with data analysis methods and Multiple Linear Regression Analysis Test through the SPSS version 23 program. The results show that the compensation variable has a positive and significant effect on Go-Ride performance. Job Satisfaction variable has a positive and insignificant effect on Go-Ride performance, and Flexibility variable has a positive and significant impact on Go-Ride performance.